Birth Order and Gender as Predictors of Career Self-Efficacy among High School Students - Inayah Ridhayanti Qarimah; Dwi Endrasto Wibowo; Zul Arsil Maulana Arief; Ribka Mutiara Simatupang; Muh. Fahmi Anugerah (ILIN Institute, 2026)
This study aimed to analyze the relationship between birth order and gender with career self-efficacy among high school students. The study was grounded in Alfred Adler’s Individual Psychology theory, particularly the concepts of family constellation and birth order, and was further supported by Social Cognitive Career Theory in explaining the development of students’ career beliefs. This research employed a quantitative correlational approach involving 174 tenth- and eleventh-grade students at SMA Negeri 1 Gowa. Data were collected using a career self-efficacy questionnaire and analyzed through Point-Biserial Correlation, Spearman Rank Correlation, and Multiple Linear Regression using IBM SPSS Statistics. The findings revealed that gender had a significant relationship with career self-efficacy, whereas birth order did not show a significant relationship. Simultaneously, gender and birth order significantly influenced career self-efficacy, although their contribution was relatively low. These findings indicate that students’ career beliefs are more strongly influenced by psychological dynamics, social experiences, and environmental support than by birth order alone.